DaaC:an architecture modeling of space information network - Shao-bo YU; Ling-da WU; Xi-tao ZHANG (Tongxin xuebao)
As a key to ensure the victory in the future high-tech war and seize the power of heaven,space information network (SIN) has important mission status and military value.The concept,connotation and operation mechanism were introduced,and the overall topology structure of SIN was discussed.The research status of SIN architecture and several typical architecture design methods were described,and the scientific issues and solutions were brought out.Combining the thought of DaaC (data as a center),an architecture model of SIN was explored.Furthermore,DaaC provides a new way for the architecture design of SIN,and the aim of the architecture modeling approach is to provide architectural support for the basic theory and key technical research of SIN.